Understand Lafaz Amr and Nahi and Their Application in Sharia Economic Law - Prayitno, Yulianto Eko (Universitas Muhammadiyah Surakarta, 2023)
One of the important concepts in understanding the Quran is the understanding of lafaz amr and nahi. Lafaz amr refers to Allah's commands in the Quran, while nahi refers to the prohibitions or restrictions of Allah SWT. In understanding lafaz amr and nahi, it is also important to understand the wisdom and purpose of Allah behind each of His commands and prohibitions. Allah's purpose is to guide mankind towards a better, harmonious life, and avoid harmful things. This research aims to explain the concept and application of lafaz amr and nahi in the context of Islamic economics. Lafaz amr and nahi are instructions or commands in Islam that are used to regulate the behaviour of individuals and society. In sharia economics, lafaz amr and nahi have an important role in maintaining the principles of justice, sustainability, and morality in economic transactions. This study uses a descriptive qualitative method by exploring and analysing literature and case studies of Islamic market regulation. The results show that the lafaz amr and nahi are used in Islamic market regulation to encourage transparency, fairness, and sustainability in various transactions. However, this research also identifies some challenges in the application of lafaz amr and nahi in Islamic economics, such as the lack of public understanding of these concepts as well as challenges in implementing Islamic economic policies that refer to lafaz amr and nahi. In conclusion, lafaz amr and nahi have an important role in maintaining the principles of Islamic economics and ensuring justice and morality in economic transactions. However, challenges in their implementation need to be overcome through community empowerment efforts and supportive policies in implementing lafaz amr and nahi in Islamic economic practices.